A vida dos produtos “ecossociais”: uma etnografia sobre consumo em tempos de capitalismo verde - Jácomo, Tiago Miguel (2020)
This Ethnography discusses - through a textual and visual narrative - what is considered an “eco-social” product as well as the social interactions involved in the production and consumption of these objects that are sold at the Pinheiros Municipal Market in São Paulo capital. The “eco-social” products are made by several traditional communities of the Brazilian Cerrado biome, those products are benefited in the Federal District. This is a multi-situated ethnography where in different fields there was the construction of a narrative that discussed the relationships between humans and objects.